Current challenges in the endovascular treatment of medium vessel occlusions - Rodriguez-Calienes, Aaron; Vivanco-Suarez, Juan; Dibas, Mahmoud; Casanova, Daniel; Galecio-Castillo, Milagros; Farooqui, Mudassir; Ortega-Gutierrez, Santiago (Frontiers in Stroke, 2023)
Medium vessel occlusions (MeVOs) account for 25%−40% of acute ischemic stroke (AIS). While mechanical thrombectomy is the standard-of-care for selected patients with large vessel occlusion (LVO), there is currently a lack of level I evidence of the safety and efficacy of endovascular treatment (EVT) for MeVOs. Several randomized clinical trials (RCTs) have attempted to answer this relevant clinical question. However, several questions related to the EVT of MeVO stroke may remain unanswered even after successful completion of these trials: What is the optimal EVT approach for secondary MeVOs? Is EVT beneficial for posterior circulation MeVOs? Is pre-EVT intravenous thrombolysis better than EVT alone? What is the optimal first line thrombectomy technique for these lesions? Are the outcome assessment tools used for LVOs appropriate for MeVOs? Upcoming evidence and the natural evolution and development of new technologies will aid in overcoming these challenges.